Jahresbericht des Vereins Kunsthalle Bern 1977 / 1978. - Gachnang, Johannes; Kunsthalle Bern (Bern : Kunsthalle Bern, 1978)
Rainer, Arnulf ; Brouwn, Stanley ; Long, Richard ; Lüpertz, Markus ; Rätz, Markus ; etc.
Duits
boek